Immunological Aspects of Candida and Aspergillus Systemic Fungal Infections. (21st January 2013) - Mueller-Loebnitz, Christoph; Ostermann, Helmut; Franzke, Anke; Loeffler, Juergen; Uharek, Lutz; Topp, Max; Einsele, Hermann
Abstract : Patients with allogeneic stem cell transplantation (SCT) have a high risk of invasive fungal infections (IFIs) even after neutrophil regeneration. Immunological aspects might play a very important role in the IFI development in these patients. Some data are available supporting the identification of high-risk patients with IFI for example patients receiving stem cells from TLR4 haplotype S4 positive donors. Key defense mechanisms against IFI include the activation of neutrophils, the phagocytosis of germinating conidia by dendritic cells, and the fight of the cells of the innate immunity such as monocytes and natural killer cells against germlings and hyphae. Furthermore, immunosuppressive drugs interact with immune effector cells influencing the specific fungal immune defense and antimycotic drugs might interact with immune response. Based on the current knowledge on immunological mechanism in Aspergillus fumigatus, the first approaches of an immunotherapy using human T cells are in development. This might be an option for the future of aspergillosis patients having a poor prognosis with conventional treatment.